Pengaruh Orientasi Pasar, Orientasi Pembelajaran, dan Orientasi Kewirausahaan terhadap Kinerja Pemasaran - Muhammad fiqron julio (JURNAL AKUNTANSI DAN MANAJEMEN, 2023)
The development of MSMEs in the city of Padang has experienced a relatively highincrease over the past 2 years, even though it was hit by Covid-19 and it is different from otherregions which generally have experienced a decline. This study aims to analyze the effect of marketorientation, learning orientation and entrepreneurial orientation on marketing performance inserving culinary MSMEs in Padang City. This study used purposive sampling for the samplingtechnique. The data were processed using SPSS version 27. The results of the study found thatmarket orientation, learning orientation and entrepreneurial orientation had a positive effect onmarketing performance. Specifically, entrepreneurial orientation has the most dominant influence,followed by learning orientation and market orientation